2008
DOI: 10.1186/1471-2180-8-117
|View full text |Cite
|
Sign up to set email alerts
|

Specific genetic markers for detecting subtypes of dengue virus serotype-2 in isolates from the states of Oaxaca and Veracruz, Mexico

Abstract: Background: Dengue (DEN) is an infectious disease caused by the DEN virus (DENV), which belongs to the Flavivirus genus in the family Flaviviridae. It has a (+) sense RNA genome and is mainly transmitted to humans by the vector mosquito Aedes aegypti. Dengue fever (DF) and dengue hemorrhagic fever (DHF) are caused by one of four closely related virus serotypes (DENV-1, DENV-2, DENV-3 and DENV-4). Epidemiological and evolutionary studies have indicated that host and viral factors are involved in determining dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…It is well accepted that immunity to a particular infectious disease governs the development of the severe form of the disease and the rapidity of its development to some extent. Host factors, such as age, nutritional state and HLA type, and vectorial factors, such as viral genotype, can also play a role in deciding the severity of disease 7,15 . Immune modulations of pregnancy are likely to contribute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that immunity to a particular infectious disease governs the development of the severe form of the disease and the rapidity of its development to some extent. Host factors, such as age, nutritional state and HLA type, and vectorial factors, such as viral genotype, can also play a role in deciding the severity of disease 7,15 . Immune modulations of pregnancy are likely to contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Host factors, such as age, nutritional state and HLA type, and vectorial factors, such as viral genotype, can also play a role in deciding the severity of disease. 7,15 Immune modulations of pregnancy are likely to contribute. Although the particular patient described by Berrington et al was born in Puerto Rico, she lived in Washington and her level of immunity to the infection was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The circulation of different serotypes and genotypes of DENV in a particular geographical region and the coexistence of two different serotypes or genotypes in a given mosquito or patient have been broadly documented [138,139,142]. Another study performed in 2007 showed that regions of the E gene underwent recombination in a patient harboring a mixed infection of DENV-1 [139].…”
Section: Dengue Virusmentioning
confidence: 99%
“…These results, although valuable as a global distribution overview, do not inform the geographic fine-mapping of dengue serotypes and genotypes which are etiologically dependent on climate and distinct viral evolution trajectories. Such microevolutionary patterns are more readily apparent in phylogeographic analyses (Cisneros et al, 2006;Gardella-Garcia et al, 2008;Pinheiro and Corber, 1997;Rico-Hesse et al, 1997).…”
Section: Introductionmentioning
confidence: 99%